2020
DOI: 10.1177/0267658320906855
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of viewpoint-taking when learning a sign language: Data from the ‘frog story’ in British Sign Language

Abstract: Little is known about how hearing adults learn sign languages. Our objective in this study was to investigate how learners of British Sign Language (BSL) produce narratives, and we focused in particular on viewpoint-taking. Twenty-three intermediate-level learners of BSL and 10 deaf native/early signers produced a narrative in BSL using the wordless picture book Frog, where are you? (Mayer, 1969). We selected specific episodes from part of the book that provided rich opportunities for shifting between differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
(68 reference statements)
2
16
0
Order By: Relevance
“…The spatial structure of sign languages is another characteristic that the research body has identified as difficult to acquire for M2 learners (e.g., McKee and McKee, 1992;Ferrara and Nilsson, 2017;Shield and Meier, 2018;Boers-Visker, 2020;Gulamani et al, 2020). The space in front of the body can be used in a range of ways, not only for articulating lexical signs but also for grammatical and discourse purposes (Perniss, 2012;Boers-Visker, 2020).…”
Section: Sign Second Language Acquisition (Ssla)mentioning
confidence: 99%
“…The spatial structure of sign languages is another characteristic that the research body has identified as difficult to acquire for M2 learners (e.g., McKee and McKee, 1992;Ferrara and Nilsson, 2017;Shield and Meier, 2018;Boers-Visker, 2020;Gulamani et al, 2020). The space in front of the body can be used in a range of ways, not only for articulating lexical signs but also for grammatical and discourse purposes (Perniss, 2012;Boers-Visker, 2020).…”
Section: Sign Second Language Acquisition (Ssla)mentioning
confidence: 99%
“…Earlier research has also looked at the use of viewpoints in L2 signers. Gulamani et al (2020) investigated the production of viewpoints in intermediate L2 learners of BSL in comparison to L1 signers. They found that character viewpoint was less used in L2 learners and concluded that character viewpoint was harder than observer viewpoint to learn.…”
Section: Sl-specific Structuresmentioning
confidence: 99%
“…To date, previous research has focused on articulation/phonological studies regarding the learning of an SL as an L2, specifically with regard to American Sign Language (Mirus, Rathmann & Meier 2001;Rosen 2004;Bochner et al 2011), but also, to some extent, British Sign Language (Ortega 2013). Furthermore, some single studies have looked at L2 acquisition of characteristic sign language structures such as depicting signs/classifier constructions (Marshall & Morgan 2015) and viewpoints of BSL (Gulamani, Marshall & Morgan 2020), and use of spatial constructions in NTS (Ferrara & Nilsson 2017). The mouth actions of hearing L2 sign language learners have so far not been studied.…”
Section: The Status Of Research On L2 Sign Languages and Mouth Actionsmentioning
confidence: 99%